Membrane aerated biofilm reactor integrated with mainstream anammox processes - Chen, Rongfen (Nanyang Technological University, 2022)
Given the absence of intrinsic nitrite oxidizing bacteria (NOB) inhibition factors and thus the emphasis on controlling oxygen availability, use of membrane aerated biofilm reactor to achieve mainstream partial nitritation/anammox (PN/A) is gaining attention. MABR allows high-efficiency direct oxygen delivery to the active biofilm and high controllability in aeration. By finetuning the lumen pressure and together with other means, it is possible to maintain a desirable oxygen availability that favours the coexistence of anaerobic ammonium oxidizing bacteria (AOB) and anaerobic ammonium oxidizing bacteria (AMX). This thesis investigated the integration of mainstream anammox processes with MABR under an exceptionally low lumen pressure (< 5kPa) that has not be reported before. MABR with microporous hollow fiber membrane in dead-end configuration was used. To prove that cross membrane oxygen influx under low lumen pressure was feasible, short-term experiments were conducted to demonstrate the catalyzing effect of active microbial activities on cross membrane oxygen transfer. Through tracking the changes in the volume and compositions of a small amount of supplied gas oxygen influx of 10.7 mg O2/m2/h was observed with half of the 50 mg-N/L influent ammonium converted to nitrite in 6h. Catalytic oxygen uptake driven by microbial activities meant that lower lumen pressure could be possible to sustain the required oxygen transfer rate. Secondly, long-term selective NOB suppression and stable partial nitritation (PN) performance under low lumen pressure were investigated alongside with a few different operating strategies. Tactics include choices of seed inoculant, ammonium loading rates, and temporary inhibitory treatment using free ammonia / free nitrous acid. Overwhelmingly, low lumen pressure is an inseparable part of an effective NOB suppression while the other factors supplemented low lumen pressure for different needs. For example, AOB-enriched inoculant resulted in quick PN startup while temporary inhibitory treatment transformed full nitrification biofilm for PN. Comparably high nitrite accumulation ratio (> 84%) and higher ammonium removal rate (> 100 mg-N/L/d) were maintained for months as compared to PN setups treated continuously with NOB inhibitory factors. Effluent mix from the PN reactors was treated with membrane biofilm inoculating with a small amount of anammox seeds. Nitrogen removal rate (NRR) of 90.1 ± 16.1 mg-N/L/d, nitrogen removal efficiency (NRE) of 70.8% ± 6.7%, and effluent TN of 11.7 ± 2.8 mg-N/L (against 50 mg-N/L ammonium in the influent) achieved were as good as those attained in various reactor configurations with bubbling aeration. Upon successfully demonstrating selective NOB suppression in the long run, synergetic coordination between AOB and AMX was further investigated in single-stage setting under minimal lumen pressure. Via lowering lumen pressure, aerobic and anaerobic ammonium oxidation rate could be synchronized to minimize interference of NOB as NOB’s access to both oxygen and nitrite was limited. Long-term PN/A with a nitrogen removal efficiency of > 70% were attained at zero externally applied pressure when two MABRs were connected in series. Furthermore, presence of organic carbon (C/N ratio ≤ 2) contributed to a further polishing of nitrate in the effluent while not affecting the overall nitrogen removal rate and efficiency. A desirable cooperation amongst different nitrogen-removing microbial groups was achieved in the membrane biofilm. Overall, this thesis offered a new perspective on the aeration pressure needed for low strength PN/A and a comprehensive discussion of the versatilities of MABR on selective NOB suppression and thus mainstream PN/A. The benefit of MABR could be further realized by tapping on the low to minimal aeration pressure used.